Niveles de resiliencia en los docentes de primaria de las instituciones públicas de Ventanilla y Callao - López Hidalgo, Iris Violeta (2012)
This comparative descriptive research aimed to compare resilience among the teachers from Ventanilla and Callao districts. The sample 286 teachers (152 from Callao and 134 from Ventanilla) of both sexes and whose labor condition were to be permanent and temporary teachers. A Resilience scale for teachers (ER-D) was applied to evaluate four factors: significant participation, self- esteen and learning, prosocial behavior and supporting perception. After processing the results, we came across to the conclusion that significant differences do not exist in the levels of resilience between the elementary school teachers of Ventanilla and Callao. Regarding the factors of significant participation, pro-social behavior and perception of support, do not exist significant differences between the teachers of both districts either. On the other hand, talking about self-esteem and learning, there are significant differences in favour of teachers of Ventanilla.